2016
DOI: 10.1111/nmo.12825
|View full text |Cite
|
Sign up to set email alerts
|

Sensory innervation of the guinea pig colon and rectum compared using retrograde tracing and immunohistochemistry

Abstract: Running Title:Extrinsic sensory nerves to rectum and colon Abbreviations:DiI; DiIC12(3) (1,1'-Didodecyl-3,3,3',3'-Tetramethylindocarbocyanine Perchlorate) or a 1:1 mixture of DiIC12 (3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…On the other hand, the relatively low number of FB+ neurons observed in this study suggest that sensory components of the vagal nerve may play more important functions in the innervation of the ICV. This is according to the previous studies, where it was found that the network of processes derived from DRG neurons in the colon is more extensive than in the stomach and jejunum [ 30 , 32 ]. This is connected with the fact that branches of the vagal nerve supply the GI tract from the oesophagus to the proximal colon [ 34 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, the relatively low number of FB+ neurons observed in this study suggest that sensory components of the vagal nerve may play more important functions in the innervation of the ICV. This is according to the previous studies, where it was found that the network of processes derived from DRG neurons in the colon is more extensive than in the stomach and jejunum [ 30 , 32 ]. This is connected with the fact that branches of the vagal nerve supply the GI tract from the oesophagus to the proximal colon [ 34 ].…”
Section: Discussionsupporting
confidence: 85%
“…The results obtained in this study indicate that the ICV, similar to other parts of the gastrointestinal tract, is supplied by neurons located in DRG [ 30 ]. Similar to previous studies, where DRG neuronal cells supplying the stomach, duodenum, ileum, and colon were described in various mammal species [ 30 , 31 , 32 , 33 ], observations made during the present investigations show that DRG plays a role in ICV sensory innervation in the domestic pig. On the other hand, the relatively low number of FB+ neurons observed in this study suggest that sensory components of the vagal nerve may play more important functions in the innervation of the ICV.…”
Section: Discussionmentioning
confidence: 97%
“…The CGRP-expressing extrinsic afferent neurons in the rodent gut (Figure 1) originate primarily from cell bodies in the dorsal root ganglia (Sternini et al, 1987;Green and Dockray, 1988;Mulderry et al, 1988;Sternini and Anderson, 1992;Robinson et al, 2004;Tan et al, 2008;Chen et al, 2016). Within the gastrointestinal tract, they supply primarily the arterial system but also project to the submucosal and myenteric nerve plexus, to the circular and longitudinal muscle layers and the lamina propria of the mucosa (Sternini et al, 1987;Su et al, 1987;Green and Dockray, 1988).…”
Section: Innervation Of the Gut By Calcitonin Gene-related Peptide-expressing Neuronsmentioning
confidence: 99%
“…27 The neuronal influence on the inflammatory state of the gastrointestinal tract in IBD is well known, 28,29 and gut immune cells express receptors for a range of neurotransmitters, including CGRP, substance P, vasoactive intestinal peptide, or nitric oxide synthase. 30,31 CGRP and its two isoforms (alpha and beta) have distinctive actions. While beta-CGRP is primarily released by primary afferent Dogiel type 2 neurons in the enteric nervous system, alpha-CGRP is liberated by neurons from the vagus nerve and the dorsal root ganglia in the spinal cord via splanchnic and pelvic nerves.…”
Section: Backg Rou N Dmentioning
confidence: 99%